IMPLEMENTING 21ST CENTURY SKILLS IN PROJECT BASED LEARNING TO DEVELOP YOUNG LEARNERS LITERACY - Wahyu Eka Prasetyaningtyas; Helda Jolanda Pentury; Anastasia Dewi Anggraeni (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
Project-based learning gives young learners an opportunity to combine the literacy of words, grammar, numbers, into productive speech and writing. In implementing a 21st century approach to developing literacy through the project-based learning, teachers need to create a learning situation which has curiosity and gives the young learners a real creative reason to learn. To do this, learning activity was set up in creative interesting projects a round. Each project has several set of creation that the young learners are led to practice with, so that they can find out more about literacy creatively by themselves. They collaborated with other learners to compare, contrast and share their learning experiences and discoveries. Finally, they made the projects creatively, displayed and presented them in groups. So, they have to be creative and innovative in creating and setting the projects through projects learning as well as to analyze and evaluate young learners’ literacy competence. Through Project-Based Learning, teachers of young learners at Kindergarten of TK Asa’adah Limo-Cinere can develop their ability to produce and communicate their literacy competence which is later can be implemented for their young learners there. They worked to define and organize ideas, inspire new topics, imagine the stories to tell, they are able to manage conceptual-problems better than those taught in common learning of literacy as well. In this case, they can write workbook or handbook for their young learners. The training of train teachers by implementing ‘21st century skills’ into the lesson of literacy, ideas, such as collaboration, critical thinking, creativity and communication are becoming effective and extraordinary purpose for the lesson itself.